“Etiology and CT pattern in patients with interstial lung disease”: shift in the trends? - Abhishek Samdesi; Alamelu Haran; Navya Chinnaswamy Narayanaswamy (The Journal of Association of Chest Physicians)
Background: Interstitial lung disease (ILD) also called as diffuse parenchymal lung diseases (DPLD) are “a diverse group of pulmonary infiltrations which result in disruption of the distal lung parenchyma characterized by both inflammation and fibrosis of lung parenchyma and is associated with wide variety of clinical situations.” The understanding of etiology and the underlying CT pattern is helpful in diagnosis, treatment initiation, assessment of response, disease prognosis, and setting up appropriate interventions to improve survival and the quality of life. Methods: A prospective observational analysis of “Radiological and Etiological patterns” in patients presenting with features of the ILD in a tertiary care hospital in South India. Results: The study consisted of 104 patients, with mean age group of 48.03 years, with female 54% of the study population. The commonest high-resolution computed tomography (HRCT) thorax pattern was usual interstitial pneumonia (UIP) (n = 52, 50%). The commonest etiology of the ILD was connective tissue disorders (CTD) (n = 59, 56.73%). Most common CTD was systemic sclerosis (n = 23, 22.11%) and rheumatoid arthritis (n = 20, 19.23%). Second most common etiology was Idiopathic Pulmonary Fibrosis (IPF) (n=15, 14.42%). The UIP pattern was observed in 59.32% patients with CTD-ILD (n = 35) and in 100% patients with the IPF. Conclusion: Connective tissue disorders was the commonest etiology (n = 59, 56.73%), followed by idiopathic etiology (n = 22, 21.15%). Unlike other studies where NSIP pattern was the commonest pattern in CTD-ILD, it was observed in our study that UIP pattern was the most common CT pattern (n = 52, 50%) in connective tissue disorders as well as other etiology of the ILDs.